(untitled) (Clinics, 2013)
OBJECTIVES: To evaluate the interobserver agreement for the Neoplastic Spine Instability Score (SINS) among spine surgeons with or without experience in vertebral metastasis treatment and physicians in other specialties. METHODS: Case descriptions were produced based on the medical records of 40 patients with vertebral metastases. The descriptions were then published online. Physicians were invited to evaluate the descriptions by answering questions according to the Neoplastic Spine Instability Score (SINS). The agreement among physicians was calculated using the kappa coefficient. RESULTS: Seventeen physicians agreed to participate: three highly experienced spine surgeons, seven less-experienced spine surgeons, three surgeons of other specialties, and four general practitioners (n = 17). The agreement for the final SINS score among all participants was fair, and it varied according to the SINS component. The agreement was substantial for the spine location only. The agreement was higher among experienced surgeons. The agreement was nearly perfect for spinal location among the spine surgeons who were highly experienced in vertebral metastases. CONCLUSIONS: This study demonstrates that the experience of the evaluator has an impact on SINS scale classification. The interobserver agreement was only fair among physicians who were not spine surgeons and among spine surgeons who were not experienced in the treatment of vertebral metastases, which may limit the use of the SINS scale for the screening of unstable lesions by less-experienced evaluators.